The Influence of Work Quality and Work Ability on the Performance of Millennial Employees of the Binjai City Government Education Office - Elfira, Viny Elfira; Absah, Yeni (Amkop Management Accounting Review (AMAR), 2025)
This research was conducted to find the effect of work quality and work ability on This research aims to analyze the influence of work quality and work ability on the millennial employee performance of the Binjai City Government Education Service. The population and samples in this research consisted of 67 millennial employees. This research employed quantitative primary data obtained through questionnaires and processed using the SPSS version 24 software. The research was conducted in 2025 with data analysis carried out using multiple linear regression models. The findings indicated that both work quality and work ability have a positive and significant influence on the millennial employee performance of the Binjai City Government Education Office, either partially or simultaneously. Work quality has a regression value of 0.120, a tcount of 3.214 and a significant value of 0.002. Work ability has a regression value of 0.474, tcount of 7.702 and a significant value of 0.000. Work quality and work ability simultaneously have a significant value of 0.000 and a Fcount value of 156.023. The most dominant variable influencing performance was the variable of work ability with the largest tcount of 7.702. Millennial Employee Performance has a very strong relationship with work quality and work ability.